Impact of antiretroviral regimen on renal transplant outcomes in HIV‐infected recipients. Issue 6 (2nd October 2018) - Sparkes, Tracy; Manitpisitkul, Wana; Masters, Brian; Bartlett, Stephen T.; Davis, Charles; Husson, Jennifer; Amoroso, Anthony; Haririan, Abdolreza
Abstract: Background: Protease inhibitors (PI) pose a challenge post‐transplant due to significant drug interactions with calcineurin inhibitors, prompting many clinicians to convert patients to non‐interacting regimens prior to transplant. The purpose of this study was to examine the impact of PI‐based regimens on graft outcomes in HIV‐infected renal transplant recipients. Methods: In this retrospective cohort study, 50 HIV‐infected renal allograft recipients (27 receiving a PI regimen, 23 receiving a non‐PI regimen) transplanted between 2003‐2015 were analyzed. Results: Cumulative rejection rates at 12 and 36 months were 41% and 54% in the PI group vs 52% and 86% in the non‐PI group. At last follow‐up, the overall risk of acute rejection in the PI group was 46% lower compared with the non‐PI cohort ( P  = 0.12). Patients who received a PI‐based regimen had significantly reduced graft failure rates ( P  = 0.027). There was no difference between groups in the degree of interstitial fibrosis/tubular atrophy, arteriolar hyalinosis, arterial sclerosis, or glomerular sclerosis on available biopsies, despite longer follow‐up time in the PI group. Conclusions: Our study suggests that PI‐based antiretroviral therapy regimens are associated with improved graft survival and that patients can achieve adequate outcomes on a PI‐based regimen when necessary. Due to study limitations, further studies are needed to determine the optimal immunosuppression/antiretroviral therapy regimen post‐transplant.